A practical guide to necropsy of the elasmobranch chondrocranium and causes of mortality in wild and aquarium-housed California elasmobranchs - Chang, Ri K.; Okihiro, Mark S. (Frontiers in Veterinary Science, 2024)
Elasmobranchs are common, iconic species in public aquaria; their wild counterparts are key members of marine ecosystems. Post-mortem examination is a critical tool for disease monitoring of wild elasmobranchs and for management of those under human care. Careful necropsy of the head, with a focus on clinically relevant anatomy, can ensure that proper samples are collected, increasing the chance of presumptive diagnoses prior to slower diagnostic workup. Immediate feedback from a thorough head necropsy allows for faster management decisions, often identifying pathogens, routes of pathogen entry, and pathogenesis, which are current shortcomings in published literature. This article proposes a protocol for necropsy of the elasmobranch chondrocranium, emphasizing unique anatomy and careful dissection, evaluation, and sampling of the endolymphatic pores and ducts, inner ears, brain, and olfactory system as part of a complete, whole-body necropsy. Extensive use of cytology and microbiology, along with thorough sample collection for histology and molecular biology, has proven effective in identifying a wide range of pathogens and assisting with characterization of pathogenesis. The cause of mortality is often identified from a head necropsy alone, but does not replace a thorough whole-body dissection. This protocol for necropsy and ancillary diagnostic sample collection and evaluation was developed and implemented in the necropsy of 189 wild and aquarium-housed elasmobranchs across 18 species over 13 years (2011-2023) in California. Using this chondrocranial approach, meningoencephalitis was determined to be the primary cause of mortality in 70% (118/168) of stranded wild and aquarium-housed elasmobranchs. Etiology was largely bacterial or protozoal. Carnobacterium maltaromaticum bacterial meningoencephalitis occurred in salmon sharks (Lamna ditropis), shortfin mako sharks (Isurus oxyrinchus), common thresher sharks (Alopias vulpinus), and one Pacific electric ray (Tetronarce californica). Miamiensis avidus was the most common cause of protozoal meningoencephalitis and found almost exclusively in leopard sharks (Triakis semifasciata) and bat rays (Myliobatis californica) that stranded in San Francisco Bay. Bacterial pathogens were found to use an endolymphatic route of entry, while protozoa entered via the nares and olfactory lamellae. Trauma was the second most common cause of mortality and responsible for 14% (24/168) of wild shark strandings and deaths of aquarium-housed animals.